THU0385 Utility of the Treatment Thresholds in Frax Proposed by the NOF and the NOGG in Patients with Breast Cancer in Adjuvant Treatment with Aromatase Inhibitors. (23rd January 2014) - Torre, I.; Perez, C.; Estopiñan, L.; Gomez, C.; Blanco, J.; Fernandez, O.; Galindez, E.; Ruiz, E.; Galve, E.; Arrazubi, V.; Sala, M. A.; Fernandez, S.; et al.
Abstract : Background: Aromatase Inhibitors (AI) are an important component in adjuvant therapy in postmenopausal women with positive estrogenic receptors in breast cancer. They inhibit the enzyme Cytochrome P450 CYP19, which causes a loss of BMD and consequently an increase in the risk of fracture. In patients with early breast cancer (EBC) in treatment with AI, it is estimated that the risk of fracture is 11% at five years. FRAX is used to calculate the probability of fracture at 10 years. Within its limitations, it should be highlighted that among its risk factors it does not include medications such as AI and that the treatment threshold adapted to patients of the Spanish population is not currently valid. Objectives: To determine if the therapeutic intervention thresholds according to the FRAX proposed by the NOF (National Osteoporosis Foundation) as well as of the NOGG (National Osteoporosis Guidelines Group) identify appropriately whether patients with early breast cancer have a high risk of fracture at the start of AI treatment. Methods: Retrospective and descriptive study of 73 patients with EBC in treatment with AI sent to the medical oncology department of a tertiary hospital (Basurto University Hospital) for monographic consultation of osteoporosis for its diagnosis, control and monitoring in the period from 01/01/2006 to 31/12/2010. A questionnaire was conducted of the risk factors, BMD DXA and FRAX. The FRAX results are described in the basal visit and the incidence of fractures in this population in December 2012 (monitoring period of 2 to 7 years). The patients with densitometric osteopenia and high risk of fracture according to the FRAX and the patients with both densitometric and established osteoporosis received treatment with bone agents by the Osteoporosis Unit. Results: The mean age of our series is 63 years (40-83). The median time from the start of the AI and the realization of the basal BMD is 4 months. The initial densitometry identified 36 patients (49%) with osteoporosis, 35 patients (48%) osteopenia and 2 patients (3%) normal. According to the FRAX applying the treatment thresholds of the NOF (FMO >= 20% and FC >=3%): 19 patients (25%) have high risk of fracture: 16 patients (21%) of FMO and 18 patients (23.6%) of FC. Applying the treatment thresholds of the NOGG in which the values vary according to age: 3 patients (4%) have high risk of fracture, 1 patient (1%) of FMO and 3 patients (4%) of FC. Of the 73 patients, 15 (20%) present fracture, all vertebral, with 5 (33%) of high risk by FRAX according to NOF and only 1 (6%) according to NOGG. Conclusions: In our series, the treatment thresholds for the FRAX of the NOF are more sensitive by identifying a greater number of patients with high risk of fracture (25%) than the NOGG (6%). Of the patients with fractures of the study (20%), only 33% of them were identified previously as high risk according to the NOF and 6% according to the NOGG. Both thresholds clearly underestimate the risk of fracture. It is necessary to validate the FRAX in prospective studies that include AI as a risk factor and apply new validated cut-off points in our population. Disclosure of Interest: None Declared